1992
DOI: 10.1111/j.1348-0421.1992.tb02034.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Type 1 and Type 3 Fimbriae on the Adherence and Pathogenesis of Salmonella enteritidis in Mice

Abstract: Through hemagglutination tests two isogenic strains of Salmonella enteritidis were shown to possess type 1 fimbriae (strain V) and type 1 and type 3 fimbriae (strain A). The two strains bound to human buccal and mouse small intestine epithelial cells. Strain A attached to the epithelial cells more readily and in larger numbers in comparison to strain V. Adherence of both strains were sensitive to the presence of D-mannose and pretreatment of the epithelial cells with tannic acid did not promote D-mannose resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…Fimbrial lectins are thought to be important in facilitating initial attachment of bacteria including salmonellae to gut epithelial cells [2,6]. However, in the present study none of the ®ve ®mbriae examined was found to be essential for attachment of bacteria to rat ileal epithelial cells in the in-vitro model used.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Fimbrial lectins are thought to be important in facilitating initial attachment of bacteria including salmonellae to gut epithelial cells [2,6]. However, in the present study none of the ®ve ®mbriae examined was found to be essential for attachment of bacteria to rat ileal epithelial cells in the in-vitro model used.…”
Section: Discussioncontrasting
confidence: 52%
“…Thus exposure of ®bronectin in basement membranes following tissue damage may provide Enteritidis with additional sites of attachment to the host intestinal epithelium. SEF21 are the most widely studied of the salmonella ®mbriae; they have been shown to contribute to the in-vitro adhesion of Enteritidis to mouse intestinal epithelial cells [6]. More recently, Ewen et al [7] demonstrated the in-vivo expression of type 1 ®mbriae by S. enterica var Typhimurium and Enteritidis following oral infection of rats.…”
Section: Introductionmentioning
confidence: 99%
“…These finding is in agreement with earlier reports by Huguette et al (1996), Alaa and Adnan (2011) which both found that the fimA gene contains sequences unique to Salmonella isolates and demonstrated that this gene is suitable for PCR target for the detection of Salmonella strains. Bacterial adherence (Kurkkonen et al, 1993) is considered to be a baseline requirement for infection, and there is evidence that many bacteria have surface appendages, such as pili or fimbriae (Clegg et al, 1985;Aslanzadeh and Paulissen, 1992), that facilitate their binding to specific receptors on the epithelial cell surface, or intestinal mucus. Although certain types of Escherichia coli fimbriae are known to be important for virulence, only type 1 fimbriae (fimA) have been implicated in Salmonella pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Others play pivotal roles in the survival of organism in the host system-mgtC (Magnesium transport C) (Blanc-Potard and Groisman 1997) or in the actual manifestation of pathogenic processes for example stn (Salmonella toxin), pip A, B, D (Marcus et al, 2000). Bacterial adherence (Kurkkonen et al, 1993) is considered to be a prerequisite for infection, and there are evidences that many bacteria have surface processes, such as fimbriae (Clegg et al, 1985;Aslanzadeh and Paulissen, 1992) or pili, that facilitate attachment to particular receptors on the epithelial cell surface, to urinary tract or intestinal mucus. Although certain strains of E. coli fimbriae are known to be important for virulence, only type 1 fimbriae (fimA) have been implicated in Salmonella pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Hemagglutinins specific for human erythrocytes have also been described previously in Escherichia coli (32,34). In addition, Salmonella strains able to agglutinate erythrocytes from a range of animals, or which show only weak hemagglutination of human erythrocytes have been reported (2,3).…”
Section: Resultsmentioning
confidence: 99%